2000
DOI: 10.1192/pb.24.2.64
|View full text |Cite
|
Sign up to set email alerts
|

Part-time training: will it lead to part-time consultant?

Abstract: There is a need for greater attention to anti-muscarinic prescribing at case conferences and the alteration of case conference treatment plans to incorporate this at the State Hospital. There is also a need for further audit or monitoring of anti-muscarinic prescribing practice at the State Hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Such findings are nevertheless consistent with the existing literatureapproximately 75% of female and 25% of male specialist registrars in medical specialties are considering working part-time as consultants (Mather, 2001). An earlier study of flexible trainees in psychiatry found that 79% wanted a part-time or job share a consultant post (Caswell & Lowe, 2000). Current job provision suggests that not all trainees will achieve this desired outcome and it is possible some will change their view on this as they approach the end of their training.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are nevertheless consistent with the existing literatureapproximately 75% of female and 25% of male specialist registrars in medical specialties are considering working part-time as consultants (Mather, 2001). An earlier study of flexible trainees in psychiatry found that 79% wanted a part-time or job share a consultant post (Caswell & Lowe, 2000). Current job provision suggests that not all trainees will achieve this desired outcome and it is possible some will change their view on this as they approach the end of their training.…”
Section: Discussionmentioning
confidence: 99%